Evaluating Interactive teaching on conceptual understanding on medium enrolment classes - S. Hatzakis, Nikos (Improving University Science Teaching and Learning, 2023)
Interactive learning is increasingly being valued as an ideal environment that promotes critical thinking, conceptual understanding, intellectual development and success. The beneficial effects of interactive lectures though very well established for small classrooms are often debated for larger classes. My hypothesis is that interactive lectures can easily be introduced to large classrooms and that students’ engagement understanding and academic achievements can be greatly improved by constructively aligned interactive lectures. The purpose of my project is to evaluate the effect of interactive teaching on students’ engagement, conceptual understanding, as well as academic achievement and performance on medium enrolment ( 55 students) classes. This is particular important for me as up to now I have been successfully implementing interactive lectures in small enrolment classes (<20 students) and now faced with the challenge to teach by myself a medium enrolment class (50 students) of the 2nd year students. To test my hypothesis I applied a series of actions on the course Nanobio 1 of the Nanoscience education some of which are shortly mentioned here: A) Interview with group of students after the end of the course. B) compare their understanding (using online tools) between subject taught using classical lecturing/preaching and subjects taught by interactive discussions C) compare students performance (grades) on subjects that are “preached” in the form of classical lectures, subject interactively discussed in the class and 338 Nikos S. Hatzakis subjects that are both interactively discussed and applied during practical exercises. My results showed a remarkable increase in correctly answering the exam question, from 45% for subjects only lectured to 70% for subjects interactively discussed and 87% for subjects interactive discussed and applied in practical exercises. Similarly online quizzes using Student Response Systems (SRS) like Socrative showed an increase from <30% to often more than 90% in students ability to apprehend and interactively discussed subject and correctly answer a multiple choice question when knowledge is attained in the form of interactive processing of information.